2018
DOI: 10.24278/2178-5031.201830104
|View full text |Cite
|
Sign up to set email alerts
|

INFLUÊNCIA DA ALTURA E DIÂMETRO DAS CEPAS NA REBROTA DE Eucalyptus SPP

Abstract: Muitas espécies de Eucalyptus apresentam alta capacidade de regeneração das cepas após o abate da árvore, o que permite conduzir o povoamento em mais de uma rotação. Sendo assim, o objetivo deste trabalho foi avaliar a influência da altura de corte e diâmetro das cepas no vigor das brotações de Eucalyptus spp. O estudo foi realizado em um povoamento de Eucalyptus spp, com espaçamento de 2,5 X 2,5 metros. A área em estudo pertence a uma empresa de base florestal, situada no município de Barra do Choça – BA. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…Stumps ranging from 10 to 15 cm in height performed better regarding the number of sprouts. Such results are in line with the study by Luz et al (2018), who reported a positive correlation between the height of the eucalyptus stumps and the amount of sprouts. When studying different cutting heights for Eucalyptus, Nascimento Filho et al (1983) obtained better results with 15 cm high stumps, whereas a height ranging from 5 to 10 cm above the ground was observed for E. Citriodora.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Stumps ranging from 10 to 15 cm in height performed better regarding the number of sprouts. Such results are in line with the study by Luz et al (2018), who reported a positive correlation between the height of the eucalyptus stumps and the amount of sprouts. When studying different cutting heights for Eucalyptus, Nascimento Filho et al (1983) obtained better results with 15 cm high stumps, whereas a height ranging from 5 to 10 cm above the ground was observed for E. Citriodora.…”
Section: Resultssupporting
confidence: 93%
“…Such results corroborate a study carried out by Luz et al (2018), which shows no positive correlation between stump diameter and number of sprouts, what may be related to a small variability among the diameter classes that were assessed. Simões et al (1972) found similar results working with Eucalyptus saligna.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations